INTERNATIONAL TOURISM IN NEW UZBEKISTAN AND ITS IMPACT ON THE LABOR MARKET - Mirolimov son of Mirislam Mirshokir (American Journals Publishing, 2024)
In the context of the rapidly growing market economy, opportunities and opportunities for the development of types are emerging in the country, further integration of the kinds into the public economy is of great importance in the country's economy. It is known from the history of the world economy that the tourism sector serves to provide currency exchange necessary for the country's treasury, to create new jobs and to raise the standard of living of the population.
Keywords: Tourism, ecotourism, logistics, population welfare, smart tourism, infrastructure, tourists, tourism goals, population welfare, regional economy, gross regional product.